Tahapan Implementasi Gerakan Literasi dalam Menguatkan Keterampilan Critical Thinking Siswa: Stages of Implementing the Literacy Movement in Strengthening Students' Critical Thinking Skills - Budi, Irwan Setia; Zahriyah, Sofiatus; Jailani, Jailani (Thawalib: Jurnal Kependidikan Islam, 2024)
Literacy movement is one of the important activities to encourage the development of students' thinking patterns. This research aims to explain and describe the stages of implementing the literacy movement in strengthening the critical thinking skills of sixth-grade students at Larangan Badung 1 State Elementary School, Pamekasan Madura. The research method used a qualitative method with a case study design. Data collection techniques: interviews with the school principal, class teachers, and students; then documentation and observation. Data analysis techniques: data condensation, presentation, and verification. Data validity checking with: source and technique triangulation. The results show that the stages include: familiarization by reading for 15 minutes before learning, development by regular visits to the public library, activities such as summarizing, discussions, and group work, application by reading together from teaching materials, digital literacy implementation using laptops and projectors for teaching material delivery, and product stage in the form of short story writing. Supporting factor: students' enthusiasm. Inhibiting factor: students not following instructions. Conclusion: the stages of digital literacy application proceed systematically. Research contribution: to ensure the sustainability and development of literacy movement activities.